The Impact of the Classroom Meeting Learning Model Integrated with Ultabi Media on Students’ Academic Achievement at SMA Nasional Makassar - Yusniar Rasjid; Muh Sri Yusal (PT ARRUS Intelektual Indonesia, 2025)
This study investigated the effect of the Classroom Meeting learning model integrated with Ultabi media on students’ learning outcomes at SMA Nasional Makassar. A pre-experimental design employing a One-Group Pretest–Post-test approach was utilized. The participants consisted of eleventh-grade students (Class XI IPA 1) selected through purposive sampling. Data were analysed using descriptive statistics and paired-sample t-test analysis. The findings revealed a substantial improvement in students’ learning outcomes. The pretest results indicated that all students (100%) were categorized at a very low achievement level, with a mean score of 64.03. After the intervention, the post-test results showed that 57.7% of students achieved a high achievement category, with a mean score increasing to 78.46. Inferential analysis demonstrated that the calculated t-value (t = 9.008) exceeded the critical t-value (1.71), with a significance value of 0.0001 (p < 0.05), indicating a statistically significant improvement. These findings suggest that integrating the Classroom Meeting learning model with Ultabi media significantly enhances students’ academic achievement. The study highlights the potential of collaborative and technology-supported learning strategies in improving classroom engagement and learning performance.